Interleukin-1R signaling is essential for induction of proapoptotic cd8 t cells, viral clearance, and pathology during lymphocytic choriomeningitis virus infection in mice - Jöckel, Lars Thomas; Wallich, Reinhard (Journal of virology, 2012)
The T cell granule exocytosis pathway is essential to control hepatotropic lymphocytic choriomeningitis virus strain WE (LCMV-WE) but also contributes to the observed pathology in mice. Although effective antiviral T cell immunity and development of viral hepatitis are strictly dependent on perforin and granzymes, the molecular basis underlying induction of functionally competent virus-immune T cells, including participation of the innate immune system, is far from being resolved. We demonstrate here that LCMV-immune T cells of interleukin-1 receptor (IL-1R)-deficient mice readily express transcripts for perforin and granzymes but only translate perforin, resulting in the lack of proapoptotic potential in vitro. LCMV is not cleared in IL-1R-deficient mice, and yet the infected mice develop neither splenomegaly nor hepatitis. These results demonstrate that IL-1R signaling is central to the induction of proapoptotic CD8 T cell immunity, including viral clearance and associated tissue injuries in LCMV infection.